2013
DOI: 10.1007/s12185-013-1278-z
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse panbronchiolitis after humanized anti-CCR4 monoclonal antibody therapy for relapsed adult T-cell leukemia/lymphoma

Abstract: We present the case of a 62-year-old Japanese woman with relapsed adult T-cell leukemia/lymphoma (ATLL) who was treated with humanized anti-CCR4 monoclonal antibody (KW-0761). Although this antibody was highly effective against refractory ATLL, 6 months after the final KW-0761 infusion, the patient complained of hypoxia due to diffuse panbronchiolitis. Physicians should remain vigilant to the possibility of such previously unreported late-onset adverse effects associated with KW-0761 therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…A post-marketing survey showed that the incidence of severe dermatological complications such as SJS and TEN was approximately 1 % in patients treated with mogamulizumab, and other complications including diffuse panbronchitis and the reactivation of hepatitis B virus have been also reported [10,11]. These unique events are considered to be immune-related triggered by the depletion of Treg.…”
Section: Discussionmentioning
confidence: 99%
“…A post-marketing survey showed that the incidence of severe dermatological complications such as SJS and TEN was approximately 1 % in patients treated with mogamulizumab, and other complications including diffuse panbronchitis and the reactivation of hepatitis B virus have been also reported [10,11]. These unique events are considered to be immune-related triggered by the depletion of Treg.…”
Section: Discussionmentioning
confidence: 99%
“…ATLL usually resists conventional chemotherapy and must be treated soon after diagnosis because of the rapid proliferation of tumor cells, which generates a high tumor burden [2,3]. In the future, novel agents, such as mogamulizumab, a humanized anti-CCR4 monoclonal antibody, might improve CBT-associated survival by decreasing the tumor burden before transplantation [32][33][34][35]. Another possibility for improving survival might be reducing the time from diagnosis to transplantation while patients with ATLL remain chemosensitive.…”
Section: Discussionmentioning
confidence: 99%
“…40 In this case, the number of CD4+CD25+FOXP3+ cells was low, and CD8+ cells had increased just before the onset of diffuse panbronchiolitis. CD8+ cells and neutrophils, together with inflammatory cytokines, are believed to play key roles in the development of diffuse panbronchiolitis.…”
Section: Diffuse Panbronchiolitismentioning
confidence: 69%